The present state and future prospects of selected business libraries in the Greater Manila Area a survey - Solivar, Victoria O.; Vallejo, Rosa M. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1975)
This is a study of ten company libraries located in the Greater Manila Area. They were selected from 26 companies which have libraries and which belong to the top 500 corporations of the Philippines for 1973. Profiles of these ten libraries and which belong to the top 500 corporations of the Philippines for 1973. Profiles of these ten libraries are given. Included in the profile are a short history of the library, its objectives, position in the organization structure, personnel, budget, layout, equipment, and a summary of major library activities.
To give more substance to the study, the author further analyzed these ten libraries in terms of their organization, collection, technical services, readers' services, personnel, finance, physical facilities, statistics maintained, inventory and annual report. The analysis revealed that the average company library is not equipped to render services which are of real value to the organization.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Business libraries -- Manila